Online Marine Satellite System Using GIS - Karpagavalli. S; V. Balamurugan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Geographic information Systems (GIS) square measure an honest tool for group action completely different form of spacial info. Its provides fast analysis and correlation of assorted geographical contexts. This method planned collects the data and integration marine data kind satellite pictures. This method automatic collects the surface location of the target. The system gets all info concerning another supply details, as well as ship movement from the automated Identification System (AIS).  The planned system creates upon immense years of expertise in style internet primarily based GIS. Internet GIS in on-line remote sensing services for ecological observation and system has solely been demo recently.